Integration of Historical and Contemporary Data Sources in Understanding the Extent and Types of Disruptions in the Syrdarya Delta Land Use/Land Cover - Zohar Zofnat; Leah Orlovsky; Isaac A. Meir (Land)
The Syrdarya Delta, located in semi-arid and arid Central Asia, is an important water source for fertile landscapes. The environmental history of the Syrdarya Delta (SD) during the 19th and 20th centuries is a diverse and understudied subject, and its natural and anthropogenic aspects changed drastically during this period. As a result of the Syrdarya Delta’s location, on the shores of the former Aral Sea, there is a vital need to expand our understanding of the phases and policies that led to the current condition. This study argues that by integrating methods from social and natural sciences and applying them to selected historical materials, among them, former classified materials from the Cold War period, we can expand our understanding regarding the extent and types of disruptions in the Syrdarya Delta ecological system. The main findings of this study show that between the second part of the 19th and the 21st centuries, a period of roughly a hundred and fifty years, the SD changed drastically in aspects of urban areas, which increased during the Soviet period, changes in land use and hydrography, with changes in the amounts, size and flowing directions of water streams in the SD. The findings also present changes in vegetative cover and amounts parallel to salinization of the soil, which increased in the 1970s–1980s, and changes in the meeting point of the former Aral Sea with the SD. The findings of the study indicate that most of these changes can be attributed to anthropogenic factors, which have taken place mainly since the 1960s–1970s under the USSR regime. As this study presents, such materials can assist in reconstructing land use and land cover from the years to which our data are limited by integrating them with modern satellite image analysis, thus being able to quantify and estimate the amounts and types of these changes regarding salinization, land use and land cover and hydrology, which are crucial for studying deltas located in arid and semi-arid landscapes, such as the SD. This study presents evidence and argues that these data are of pivotal importance and should be used when attempting to rehabilitate and manage today’s Syrdarya Delta landscapes and hydrology.